2015
DOI: 10.3233/jbr-150088
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation kinetics of monomeric anthocyanins, colour changes and storage effect in elderberry juices

Abstract: BACKGROUND: Elderberry (Sambucus nigra L.) is considered an interesting fruit as food ingredient, due to its high content of anthocyanins that give products an attractive red colour. OBJECTIVE: The aim of present study was to evaluate the kinetics of elderberry monomeric anthocyanin (MAcy) and colour degradation due to thermal processing and storage. METHODS: Anthocyanins content was measured with pH-differential method. CIELab parameters were obtained with a Minolta Spectrophotometer, total phenolics were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
1
14
2
2
Order By: Relevance
“…The anthocyanin content of roselle juice was ranged from 63.04±2.19 to 83.74±2.17 mg/100 mL of the sample (Table 1). The amount of anthocyanin content in roselle juice without GA (83.74±2.17 mg/100 mL) was lower than reported in elderberry juice (96.4±4.8mg/100 mL) and mulberry concentrate (223.3mg/100 mL) as reported by Casati et al (2015) and Kara and Ercelebi (2013), respectively. Nevertheless, the value was higher than reported in blackcurrant juice, pomegranate juice and roselle juice in previous studies (Turfan et al, 2011;Ibrahim and Mazuki, 2013;Dobson et al, 2017).…”
Section: Total Anthocyanin Contentcontrasting
confidence: 47%
“…The anthocyanin content of roselle juice was ranged from 63.04±2.19 to 83.74±2.17 mg/100 mL of the sample (Table 1). The amount of anthocyanin content in roselle juice without GA (83.74±2.17 mg/100 mL) was lower than reported in elderberry juice (96.4±4.8mg/100 mL) and mulberry concentrate (223.3mg/100 mL) as reported by Casati et al (2015) and Kara and Ercelebi (2013), respectively. Nevertheless, the value was higher than reported in blackcurrant juice, pomegranate juice and roselle juice in previous studies (Turfan et al, 2011;Ibrahim and Mazuki, 2013;Dobson et al, 2017).…”
Section: Total Anthocyanin Contentcontrasting
confidence: 47%
“…This includes during the enzymatic processing of fruit before juice pressing, which in turn allows for the better extraction of anthocyanins responsible for the color of berry juices [37]. However, many scientific studies point to the negative effect of thermal treatment on the stability of anthocyanins, which can easily degrade at higher temperatures [38][39][40]. Nevertheless, Casati et al [38] obtained interesting results when they studied the effect of heat treatment times on elderberries at 90 • C, 80 • C, and 70 • C, on the kinetics of anthocyanin degradation.…”
Section: Anthocyanin and Total Phenolic Contentmentioning
confidence: 99%
“…However, many scientific studies point to the negative effect of thermal treatment on the stability of anthocyanins, which can easily degrade at higher temperatures [38][39][40]. Nevertheless, Casati et al [38] obtained interesting results when they studied the effect of heat treatment times on elderberries at 90 • C, 80 • C, and 70 • C, on the kinetics of anthocyanin degradation. It turned out that the higher the temperature, the greater the degree of anthocyanin degradation, but the duration of thermal treatment is also very important.…”
Section: Anthocyanin and Total Phenolic Contentmentioning
confidence: 99%
“…Similarly, Assous et al (2014) reported that purple carrots contain 168.7 mg anthocyanins/100 g fresh weight, and the major constituents were found as cyanidin-3-xylosyl-glucosyl-galactoside Color of the extracts is related with total anthocyanin content as expected (Khandare et al 2011). On the other hand, color degradation might be slower than the anthocyanin degradation at the same temperature (Casati et al 2015). The percent polymeric color value for unstored fruit or vegetables is generally less than 10 % (Türkyılmaz et al 2012).…”
Section: Discussionmentioning
confidence: 99%